Vital Roles of Gremlin‐1 in Pulmonary Arterial Hypertension Induced by Systemic‐to‐Pulmonary Shunts. Issue 15 (4th August 2020) - Meng, Liukun; Teng, Xiao; Liu, Yao; Yang, Chao; Wang, Shengwei; Yuan, Wen; Meng, Jian; Chi, Hongjie; Duan, Lihua; Liu, Xiaoyan
Abstract : Background: Heterozygous mutation in BMP (bone morphogenetic protein) receptor 2 is rare, but BMP cascade suppression is common in congenital heart disease–associated pulmonary arterial hypertension (CHD‐PAH); however, the underling mechanism of BMP cascade suppression independent of BMP receptor 2 mutation is unknown. Methods and Results: Pulmonary hypertensive status observed in CHD‐PAH was surgically reproduced in rats. Gremlin‐1 expression was increased, but BMP cascade was suppressed, in lungs from CHD‐PAH patients and shunted rats, whereas shunt correction retarded these trends in rats. Immunostaining demonstrated increased gremlin‐1 was mainly in the endothelium and media of remodeled pulmonary arteries. However, mechanical stretch time‐ and amplitude‐dependently stimulated gremlin‐1 secretion and suppressed BMP cascade in distal pulmonary arterial smooth muscle cells from healthy rats. Under static condition, gremlin‐1 significantly promoted the proliferation and inhibited the apoptosis of distal pulmonary arterial smooth muscle cells from healthy rats via BMP cascade. Furthermore, plasma gremlin‐1 closely correlated with hemodynamic parameters in CHD‐PAH patients and shunted rats. Conclusions: Serving as an endogenous antagonist of BMP cascade, the increase of gremlin‐1 in CHD‐PAH may present a reasonable mechanism explanation for BMP cascade suppression independent of BMP receptor 2 mutation.